Measurement of consumer price changes by income classes - Iochi, Ryotaro (Tokyo, Japan : Kinokuniya Book-Store Co., 1964)
This is a memorandum to those who are interested in the problem of divergence of price impact among income groups.
sju 21/01/2019
Loans